2017
DOI: 10.1111/tid.12757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbapenem‐resistant Klebsiella pneumoniae (CRKP) infections in kidney transplantation

Abstract: The study confirmed that a CR-KP positivity may affect the outcome of a kidney transplant population. In severe CR-KP infections with sepsis, a combined antibiotic treatment seems to be advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…Most of current antibiotics utilized in practice have no therapeutic effect on CRKP infection after renal transplantation, with the mortality can be as high as 40% to 70% [55,56], and the 30-days mortality rate was 50% to 60% [57,58]. In recent years, the resistance rate of CRKP to polymyxin and tigecycline was increasing [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Most of current antibiotics utilized in practice have no therapeutic effect on CRKP infection after renal transplantation, with the mortality can be as high as 40% to 70% [55,56], and the 30-days mortality rate was 50% to 60% [57,58]. In recent years, the resistance rate of CRKP to polymyxin and tigecycline was increasing [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of CRE infection following SOT depends on geography, occurrence of local outbreaks, patterns of resistance, and the organ transplanted. The risk is documented to range from 0.4 to 26.3%, but the majority of data is limited to single-center studies analyzing abdominal organ transplant recipients (Table 2) [22,[34][35][36][37][38][39][40][41][42][43][44][45]. In the USA, the incidence of CRE infection posttransplant is less than 10% [35-37, 42, 43], but in Brazil the risk can be as high as 26% in renal transplant patients [34].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
“…However, a national surveillance program in Italy reported that 26.5% of all Gram-negative isolates from SOT recipients were carbapenem resistant [46]. Most CRE infections occur within the first 3 months after transplant, but the median or mean time from transplant to infection ranges from 11 to 218 days [22,[34][35][36][37][38][39][40][41][42][43][44][45]47].…”
Section: Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%
See 2 more Smart Citations